The culture map : decoding how people think, lead, and get things done across cultures - Meyer, Erin, 1971- (New York : INGRAM PUBLISHER SERVICES US, 2016)
Whether you work in a home office or abroad, business success in our ever more globalized and virtual world requires the skills to navigate through cultural differences and decode cultures foreign to your own. Renowned expert Erin Meyer is your guide through this subtle, sometimes treacherous terrain where people from starkly different backgrounds are expected to work harmoniously together.When you have Americans who precede anything negative with three nice comments French, Dutch, Israelis, and Germans who get straight to the point ( your presentation was simply awful ) Latin Americans and Asians who are steeped in hierarchy Scandinavians who think the best boss is just one of the crowd,the result can be, well, sometimes interesting, even funny, but often disastrous.Even with English as a global language, it's easy to fall into cultural traps that endanger careers and sink deals when, say, a Brazilian manager tries to fathom how his Chinese suppliers really get things done, or an American team leader tries to get a handle on the intra-team dynamics between his Russian and Indian team members.In The Culture Map, Erin Meyer provides a field-tested model for decoding how cultural differences impact international business. She combines a smart analytical framework with practical, actionable advice for succeeding in a global world.
Keywords: Interculturele communicatie